2021
DOI: 10.1371/journal.pcbi.1009435
|View full text |Cite
|
Sign up to set email alerts
|

Separable actions of acetylcholine and noradrenaline on neuronal ensemble formation in hippocampal CA3 circuits

Abstract: In the hippocampus, episodic memories are thought to be encoded by the formation of ensembles of synaptically coupled CA3 pyramidal cells driven by sparse but powerful mossy fiber inputs from dentate gyrus granule cells. The neuromodulators acetylcholine and noradrenaline are separately proposed as saliency signals that dictate memory encoding but it is not known if they represent distinct signals with separate mechanisms. Here, we show experimentally that acetylcholine, and to a lesser extent noradrenaline, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 126 publications
(251 reference statements)
0
3
0
Order By: Relevance
“…Complementarily, a common excitatory input to these cell types that is activated during immobility could explain their sustained immobility activation. Although such an input remains to be found, neuromodulatory afferents are attractive candidates (Atherton et al, 2015; Kaufman et al, 2020; Prince et al, 2021), as they have been shown to regulate interneuron dynamics during locomotion/immobility in the neocortex (Fu et al, 2014). Of particular interest, serotonergic afferents from the median raphe have been shown to selectively target CCK and CB cells in CA1 (Freund et al, 1990; Varga et al, 2009), and certain serotonin receptor subtypes are depolarizing and restricted to CGE- derived interneurons (5-HT3AR).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complementarily, a common excitatory input to these cell types that is activated during immobility could explain their sustained immobility activation. Although such an input remains to be found, neuromodulatory afferents are attractive candidates (Atherton et al, 2015; Kaufman et al, 2020; Prince et al, 2021), as they have been shown to regulate interneuron dynamics during locomotion/immobility in the neocortex (Fu et al, 2014). Of particular interest, serotonergic afferents from the median raphe have been shown to selectively target CCK and CB cells in CA1 (Freund et al, 1990; Varga et al, 2009), and certain serotonin receptor subtypes are depolarizing and restricted to CGE- derived interneurons (5-HT3AR).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, subsets of medial septal GABAergic cells have been shown to selectively target AACs and CCKs in CA3 (Joshi et al, 2017), and some medial septal GABAergic cells have been shown to be activated during hippocampal SWRs (Viney et al, 2013). However, many subcortical areas have been shown to be modulated before SWRs (Logothetis et al, 2012), some of which have known afferents to the hippocampus (Atherton et al, 2015; Prince et al, 2021). This also includes subsets of raphe cells (Varga et al, 2009) that decrease their firing rate approximately one second before SWRs (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus is crucial for memory storage and conversion ( Mujawar et al, 2021 ; Prince et al, 2021 ). It contains the CA1–4 region, which is mainly composed of pyramidal neurons.…”
Section: Discussionmentioning
confidence: 99%